L'anticorps (sportif) et le contre-pied (subversif). Biopolitique du corps antisportif dans la bande dessinée franco-belge. Issue 2 (4th May 2018) - Robert, Pascal
Abstract : In most cases, adventure comic heroes have bodies fit for sports. However, in humorous comic strips, in particular, some heroes, or rather anti-heroes, cannot be said to have the body of a sportsman – they even oppose that ideal in any and every way. This paper examines such bodies from a semiotic perspective in order to determine what they are and what they do compared to fitter bodies, as well as reveal their subversive agenda. The present work deals with several Franco-Belgian comic classics ( Gaston, Achille Talon, Iznogoud, Asterix and Obelix ) and aims to show how such bodies subvert social activities, the bourgeois lifestyle, sports practices, and the exercise of power. Their subversion is political, or rather infrapolitical, and may belong to biopolitics as defined by Foucault.